Using Bilingual Examinees to Evaluate the Comparability of Test Structure across Different Language Versions of a Mathematics Exam - Sukin, Tia (2015)
Malay- and English-language versions of a mathematics exam were analyzed for structural equivalence byadministering both versions to a group of Malay-English bilingual students. The analysis and comparison of test structure was determined using both DIMTEST and weighted multidimensional scaling. The assessment was found to be unidimensional and to possess similar structure across the two language versions. Implications of this study suggest bilingual examinees can be used to evaluate the invariance of test structure across translated test forms. Future research should explore situations where bilingual examinees can be used to link different language versions of assessments for monolingual populations.